Dating the Shift to English in the Financial Accounts of Some London Livery Companies: A Reappraisal - Alcolado Carnicero, José Miguel (Multilingua: Journal of Cross-Cultural and Interlanguage Communication, 2017)
A mixed-language phenomenon such as language shift has been acknowledged to constitute one of the hallmarks of the manuscripts in which the members of the City of London livery companies recorded their financial transactions during the late medieval period. Despite these texts having been studied by scholars in very diverse disciplines, inconsistencies pertaining to the exact date when some companies shifted from Latin and/or French to English as their official language of record keeping have prevailed in the literature. This article is intended to shed light on the evolution over time of language shift in different livery companies, by revisiting the two single studies which, albeit marginally, have so far touched on this topic (Heather Creaton's [1976] edition and translation of the London Mercers' Wardens' Accounts and Lisa Jefferson's [2003] edition and translation of the London Goldsmiths' Wardens' Accounts and Court Minutes), and by contrasting each perspective with linguistic information from first-hand sources. I conclude that there remains a need for a much more consistent and focused approach to the issue of language shift in the City of London livery companies.
Keywords: historical linguistics; language shift; written language mixing; Latin; French; english; financial accounts; London livery companies; JCR; Scopus